Learning by Doing : Uganda’s AIDS Control Project Empowers Local Managers - Valadez, Joseph J.; Nsubuga, Peter (World Bank, Washington, DC, 2012)
Surveillance systems in Uganda detect that HIV prevalence declined from 21.1 percent in 1991 to 6.4 percent in 2001. The most common explanations for this decrease are that the population mobilized itself with the consequence that more people were faithful to their partners, or abstained from sexual contact, and used condoms during sexual intercourse (Low-Beer et al 2003). Although one might debate which of these behavior changes contributed most to the apparent reduction in HIV prevalence, no one would claim that Uganda can now become complacent about its HIV/AIDS programs. Quite the contrary. National HIV/AIDS Committees continue to have the responsibility for both covering their populations with the highest quality prevention, care, support, and treatment programs possible, and to improve them constantly.